SOCIOCULTURAL REMINISCENCIES OF PANDEMICS, HEALTH CULTURE AND TOURISM IN DALMATIA - Stanko Geić; Marijana Jurišić; Jakša Geić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Throughout its millennial history, humanity has been confronted with numerous infectious diseases and even global pandemics since time immemorial, with an insufficient level of health culture. Among the most famous and most terrible pandemics, the source and focus of which was most often in the Far East with a low health culture were pandemics of leprosy, plague, smallpox, cholera, tuberculosis, malaria, and the latest pandemic Corona virus SARS cov-2 covid-19 They also aff ected our region and Dalmatia, which has always had extensive communications throughout the Mediterranean and the world. Half a billion people or 2/3 of the inhabitants of Europe and its recurrences are recorded until the beginning of the 21st century. The development of mass tourism with all the health benefits of temporary changes in the working and living environment and living in healthsaving areas (sea, lakes, mountains ...), due to large globalized intercontinental migrations at the same time results in large pollution and environmental destruction and intensive contacts for the spread of epidemics pai pandemic infectious diseases.Positive but also negative experiences and the scale of pandemics of infectious diseases and activities for their prevention and control are considered on a global scale and especially in the area of the famous Croatian Mediterranean region of Dalmatia, as a crossroads of demographic, economic and cultural communications to Europe and the world. Understanding and analyzing the occurrence and legality of occurrence, development, spread and duration of periodic recurrence of epidemics and pandemics, as well as their suppression and prevention throughout the millennium history, with sociocultural and touristic interaction which is discussed in this paper, can be a valuable reference point in the current pandemic SARS Cov-2 Covid 19, which has seriously threatened the world with so far (31.01.21.) an estimated over 100 million patients and 2 million deaths ( in Croatia over200 000 patients and 5000 deaths) with, in some european countries, a worrying progression that despite the efforts of the health epidemiological profession is not waning. However, with the drastic measures taken by the National Staff , the situation with the pandemic at the end of January 2021 is gradually easing, which allows for a cautious relaxation of measures. Following this is the announcement of further cautious easing of measures with the intention that Croatia, as a “corona free” destination, welcomes the upcoming tourist season on which the entire Dalmatian and whole Croatian economy depends.